White parents, black children : experiencing transracial adoption - Smith, Darron T., 1965- (Rowman & Littlefield Publishers, 2011)
With increasing numbers of transracial adoptions in the U.S., White Parents, Black Children brings to light the difficult racial issues that are often challenging for families to talk about. This book is written to help parents, educators, and others wo.